Aircraft engines and gas turbines - Kerrebrock, Jack L. (Cambridge, Mass. : MIT Press, 1992)
Covering all types of modern aircraft engines, including turbojets, turbofans and turboprops, this text treats the engine as a complete system at increasing levels of sophistication, and also discusses hypersonic propulsion systems of the future.
Includes bibliographical references and index.
Keywords: Aircraft gas-turbines.; Aircraft gas-turbines; Aircraft -- Engines